The effect of radiant flux density on soybean nodulation - Melges, Elena; Lopes, Nei F.; Oliva, Marco A.; Gomes, Maria M. Souza (Pesquisa Agropecuaria Brasileira, 2014)
The effect of light flux density (30%, 50%, 70% and 100% of sunlight) on soybean (Glycine max (L.) Merrill cv. UFV-2) nodulation was studied under field conditions. Shade reduced the number, dry weight, growth rate of nodules, and also accelerated their senescence. Nodule number, dry weight and growth rate decayed quickly during pod filling, evidencing a competition for assimilate between seeds and nodules. Nitrogen content was shown to be related to light flux density.